Impedance-based method for DC stability of VSC-HVDC system with VSG control. (September 2021) - Li, Chang; Cao, Yijia; Yang, Yaqian; Wang, Lei; Blaabjerg, Frede; Dragicevic, Tomislav
Highlights: This article proposes a VSG CONTROL method to dampen oscillation of DC voltage, improve damping performance as well as inertia. This paper analyzed the mechanism of VSG damping oscillation and improving damping performance of DC voltage in the framework of impedance modeling. Abstract: DC-side oscillation problems trouble the stable and secure operation of voltage source converter high voltage direct current (VSC-HVDC) systems. Therefore, it is of considerable significance to investigate the physical origins of these oscillations. Thus, this paper proposes an impedance-based method for VSC-HVDC system DC stability analysis. Differently, a new perspective for DC resonance interaction is introduced, which is judged by the interactive behavior of two subsystems impedances, namely converter impedance and DC network impedance. Also, the proposed method quantitatively estimates the damping of DC schemes of VSC-HVDC system. Based on the proposed method, it is found that the global stability of VSC-HVDC system can be guaranteed if and only if: 1) subsystems are passive and locally stable, 2) there is no resonance interaction between inductive impedance and capacitive impedance, and 3) damping of DC system is large enough. Moreover, another contribution is to apply the virtual synchronous generator (VSG) control technique in VSC-HVDC system to dampen DC-side oscillation caused by impedance interaction. Specifically, this VSG control enhances inertia and damping of VSC-HVDC system on DC-side. Finally, the feasibility of the proposed technique and the accuracy of the mathematical model are demonstrated through simulation and experimental results.